Do Economic Crises Lead Tourists to Closer Destinations? An Analysis of Italy's Regional Data - Gianluca Cafiso; Roberto Cellini; Tiziana Cuccia (Center for Economic Studies and ifo Institute (CESifo), 2015)
This article investigates whether the distance between origin and destination has played an increased role in shaping Italy's domestic tourism flows during the recent years of economic recession. Indeed, the occurrence of closer tourism destinations, as a consequence of the economic crisis, has been recently suggested by a number of authors who obtain their results from micro-data and, more specifically, from surveys. Differently, we study this issue through aggregate official data. Our dataset is made of inter-regional tourism flows among Italian regions over the 2000-12 period; across this period, 2008 to 2012 are years of economic recession. The analytical tool employed is a gravity model. Our results document that distance played a more and more relevant role during the recession.
Keywords: L83; R12; C29; 330; tourism; gravity mode; regions; distance; great recession